PROGRESSIVE ISLAMIC THEOLOGY AS A THIRD PATHWAY IN ABDULLAH SAEED’S CONTEMPORARY REVIVAL THOUGHT - Firdaus, Fiqih; Nurhayati, Aniek (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This article discusses Abdullah Saeed's thoughts regarding the need for a progressive Islamic discourse for the rise of Islam in the contemporary era. Saeed sees the need to have a dialogue between the treasures of the legacy of classical scholars and the current developments of modern science. Of course, the treasures of the legacy of the classical scholars must be read in depth and critically to find common ground with the socio-historical modern Muslims. The proposed method is using a contextualism approach, namely reading verses by not only looking at the textual side of the universal meaning, but also looking at the context in which Muslims live.